Expert Review on Nonsurgical Management of Parapneumonic Effusion: Advances, Controversies, and New Directions - Fitzgerald, Deirdre B.; Polverino, Eva; Waterer, Grant W. (Seminars in Respiratory and Critical Care Medicine, 2023)
Parapneumonic effusion and empyema are rising in incidence worldwide, particularly in association with comorbidities in an aging population. Also driving this change is the widespread uptake of pneumococcal vaccines, leading to the emergence of nonvaccine-type pneumococci and other bacteria. Early treatment with systemic antibiotics is essential but should be guided by local microbial guidelines and antimicrobial resistance patterns due to significant geographical variation. Thoracic ultrasound has emerged as a leading imaging technique in parapneumonic effusion, enabling physicians to characterize effusions, assess the underlying parenchyma, and safely guide pleural procedures. Drainage decisions remain based on longstanding criteria including the size of the effusion and fluid gram stain and biochemistry results. Small-bore chest drains appear to be as effective as large bore and are adequate for the delivery of intrapleural enzyme therapy (IET), which is now supported by a large body of evidence. The IET dosing regimen used in the UK Multicenter Sepsis Trial -2 has the most evidence available but data surrounding alternative dosing, concurrent and once-daily instillations, and novel fibrinolytic agents are promising. Prognostic scores used in pneumonia (e.g., CURB-65) tend to underestimate mortality in parapneumonic effusion/empyema. Scores specifically based on pleural infection have been developed but require validation in prospective cohorts.
Keywords: parapneumonic effusion; pleural infection; empyema; intrapleural enzyme therapy